Insights into the hydrogenation mechanism of nitrobenzene to aniline on Pd3/Pt(111): a density functional theory study. Issue 43 (14th May 2015) - Zhang, Lianyang; Jiang, Junhui; Shi, Wei; Xia, Shengjie; Ni, Zheming; Xiao, Xuechun
<x xml:space="preserve">Abstract</x> The hydrogenation mechanism of nitrobenzene to aniline on Pd3/Pt(111) surface preferentially follows the direct route and fits best the Jackson reaction mechanism (mechanism B).